Effect of three representative surfactants on methane hydrate formation rate and induction time - Mostafa keshavarz Moraveji; Ahmadreza Ghaffarkhah; Arash Sadeghi (Egyptian Journal of Petroleum)
The effects of three types of surfactants on methane hydrate formation process were investigated. Three different classes of surfactants involving anionic (sodium dodecyl sulfonate), cationic (hexadecyl trimethyl ammonium bromide) and non-ionic (poly oxy ethylene (40) octyl phenyl ether) have been used. Thermodynamics of hydrate formation, formation rate, kinetic constants and induction time in the presence of surfactants with various concentrations were analyzed. Critical micelle concentrations (CMCs) of these surfactants in water were determined by induction time measurements in various concentrations under methane hydrate formation conditions. The critical micelle concentration (CMC) at the methane hydrate formation conditions for SDS, HTABr and TritonX-405 solutions were obtained at 450, 380 and 950 ppm, respectively. The experimental results indicated that hydrate formation rate increased with the use of surfactants for all concentrations and induction time decreased. It was found that for surfactants, CMC at hydrate formation conditions was less than CMC at ambient conditions.